(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This article analyzes the relationship between digital citizenship and the republican principle, focusing on the influence of algorithms on political debate on social networks. Citizenship, essential for republican legitimacy, is expanded in the digital environment, where citizens exercise civil, political and social rights. However, the use of algorithms on digital platforms presents democratic challenges, such as the creation of information bubbles and echo chambers, which can limit the pluralism of ideas and public debate. In addition, algorithmic manipulation can introduce despotic characteristics into the interactions between users and digital systems. The article proposes that digital platforms should be held responsible for protecting the plurality of ideas and guaranteeing citizens’ informational self-determination, seeking to promote a more inclusive and resilient democracy in the digital environment.